Auditory neuropathy in Brown–Vialetto–Van Laere syndrome due to riboflavin transporter RFVT2 deficiency. (25th February 2016) - Menezes, Manoj P; O'Brien, Katherine; Hill, Mandy; Webster, Richard; Antony, Jayne; Ouvrier, Robert; Birman, Catherine; Gardner‐Berry, Kirsty
Abstract : Aim: Mutations in the genes encoding the riboflavin transporters RFVT2 and RFVT3 have been identified in Brown–Vialetto–Van Laere syndrome, a neurodegenerative disorder characterized by hearing loss and pontobulbar palsy. Treatment with riboflavin has been shown to benefit individuals with the phenotype of RFVT2 deficiency. Understanding the characteristics of hearing loss in riboflavin transporter deficiency would enable early diagnosis and therapy. Method: We performed hearing assessments in seven children (from four families) with RFVT2 deficiency and reviewed results from previous assessments. Assessments were repeated after 12 months and 24 months of riboflavin therapy and after cochlear implantation in one individual. Results: Hearing loss in these individuals was due to auditory neuropathy spectrum disorder (ANSD). Hearing loss was identified between 3 years and 8 years of age and progressed rapidly. Hearing aids were not beneficial. Riboflavin therapy resulted in improvement of hearing thresholds during the first year of treatment in those with recent‐onset hearing loss. Cochlear implantation resulted in a significant improvement in speech perception in one individual. Interpretation: Riboflavin transporter deficiency should be considered in all children presenting with an auditory neuropathy. Speech perception in children with ANSD due to RFVT2 deficiency may be significantly improved by cochlear implantation. What this paper adds: Hearing loss is a presenting or early feature in Brown–Vialetto–Van Laere syndrome caused by riboflavin transporter RFVT2 deficiency. Hearing loss in RFVT2 deficiency is due to auditory neuropathy spectrum disorder (ANSD). Early treatment with riboflavin may improve hearing thresholds in addition to motor phenotype. Hearing aids are not beneficial but cochlear implantation may improve speech perception. Riboflavin transporter deficiency should be considered in all children presenting with ANSD.